2012
DOI: 10.1002/jmor.20086
|View full text |Cite
|
Sign up to set email alerts
|

Cornification in reptilian epidermis occurs through the deposition of keratin‐associated beta‐proteins (beta‐keratins) onto a scaffold of intermediate filament keratins

Abstract: The isolation of genes for alpha-keratins and keratin-associated beta-proteins (formerly beta-keratins) has allowed the production of epitope-specific antibodies for localizing these proteins during the process of cornification epidermis of reptilian sauropsids. The antibodies are directed toward proteins in the alpha-keratin range (40-70 kDa) or beta-protein range (10-30 kDa) of most reptilian sauropsids. The ultrastructural immunogold study shows the localization of acidic alpha-proteins in suprabasal and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…The lack of nuclear labeling for beta‐catenin during this stage suggests that alpha keratinization is the basic (“default”) program of differentiation present in lizard keratinocytes, confirming previous views (Flaxman, ; Maderson et al, ). As shown in Figure A, it appears that when beta‐cells are produced in the central region of the elongating pegs this constitutive program is changed and newly synthesized proteins are deposited onto the alpha‐keratin scaffold present in beta‐cells (Alibardi, ). This is evidenced by the nuclear labeling for beta‐catenin that becomes temporary visible, especially in basal cells of the elongating caudal side of the pegs at Stages 2–3 of the shedding cycle, destined to produce new keratinocytes for the formation of the Oberhäutchen and beta‐layer.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of nuclear labeling for beta‐catenin during this stage suggests that alpha keratinization is the basic (“default”) program of differentiation present in lizard keratinocytes, confirming previous views (Flaxman, ; Maderson et al, ). As shown in Figure A, it appears that when beta‐cells are produced in the central region of the elongating pegs this constitutive program is changed and newly synthesized proteins are deposited onto the alpha‐keratin scaffold present in beta‐cells (Alibardi, ). This is evidenced by the nuclear labeling for beta‐catenin that becomes temporary visible, especially in basal cells of the elongating caudal side of the pegs at Stages 2–3 of the shedding cycle, destined to produce new keratinocytes for the formation of the Oberhäutchen and beta‐layer.…”
Section: Discussionmentioning
confidence: 99%
“…In the regenerating epidermis, retinol and/or its derived metabolites have shown to inhibit the process of keratinization (accumulation of IF‐keratins) and the following cornification (addition of corneous and keratin‐associated proteins to the keratin framework; see Alibardi, ). This interference was previously noted in the avian and mammalian epidermis and keratinocytes cultivated in vitro (Barnett & Szabo, ; Chopra and Flaxman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other sections of tissues embedded in Bioacryl were immunostained for the detection of CBPs (formerly indicated as β‐keratins) using a rabbit antibody (precore box, see Alibardi, ). Briefly, the sections were preincubated for 20 min in 0.1 M Tris buffer solution at pH 7.4, with the addition of 5% of bovine serum albumin for blocking nonspecific antigenic sites.…”
Section: Methodsmentioning
confidence: 99%
“…A further indication that true intermediate filament keratins (alpha‐keratins) mix and interact with beta‐proteins during epidermal maturation derives from the detection of immunolabeled bands in 1D Western blots or immunolabeled spots in 2D Western blots within the range of alpha‐keratins, above 40 kDa (Alibardi and Toni, ; Rizzo et al, ; Toni et al, ). Also double‐labeling studies using immunogold at the ultrastructural level demonstrated the coexpression and mixing of these two types of proteins (Alibardi, ).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins have been provisionally subdivided into 4 subfamilies: High Glycine (HgG, 17 members), High Glycine Cysteine (HGC, 16 members), High Cysteine (HC, 2 members), and Low Glycine and Cysteine (LwGC, 2 members). Systematic immunohistochemical studies have mapped the distribution of representative members of the above 37 CBPs in the skin of A. carolinensis (Alibardi et al, ; Alibardi, ). The presence of so many small CBPs suggests that these proteins mix in different proportion in scales localized in different body areas to impart them their specific mechanical or barrier performances.…”
Section: Introductionmentioning
confidence: 99%